KURIKULUM ADAB PERSPEKTIF IBNU JAMA’AH DI DALAM KITAB TADZKIRATU AL-SAMI’ WA AL-MUTAKALLIM - Latif Maulana; Didin Hafiduddin (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2022)
Making students have commendable character is the most important goal of Islamic education so that it should become a complete curriculum. The position of adab and morals is placed in a very, very high position, so that a lot of concepts are found for the unification of knowledge, etiquette and morals as if two elements cannot be separated from one another. However, in reality there are still many educational institutions, including pesantren, which are minimal in habituation of manners and noble character. It is necessary to organize and organize an adab curriculum that reflects on the Qur'an and Sunnah as well as the salaf al-shalih. Thus, the researcher wants to discuss the curriculum of students' etiquette according to Ibn Jama'ah in his book Tadzkirah Al-Sami' Wa Al-Mutakallim Fi Adab Al-'Alim Wa Al-muta'allim. In this research, the writer uses a general method, namely library research which is combined with descriptive method. In general, the adab curriculum according to Ibn Jama'ah can be grouped into three types, namely: student etiquette towards himself, student etiquette in learning in an educational environment, and student etiquette when hanging out with friends. Thus, after students pass the adab curriculum, when studying, they should have sincere intentions because Allah ta'la, have the nature of Zuhud (not concerned with worldly life), Wara' (be careful), Tawadhu' (not arrogant), Qana' ah (feeling enough), patience, and other commendable traits.